A search model of optimal pricing and production - Steve Alpern; Dennis J. Snower (Centre for Economic Policy Research (CEPR); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
This paper presents an overview of the application of the mathematical theory of 'high-Iow' search to firms' pricing and production decisions. We show how this methodology can be used to determine an optimal sequence of price-quantity decisions by a firm through time. We suppose that the firm chooses a sequence of prices and quantities supplied over time not only with a view to earning current profit (given the current information about the demand curve) but also in order to acquire information about the demand curve by observing its inventory stocks as a result of these price and quantity decisions. We compare and contrast the high-Iow model with the conventional microeconomic model of pricing and production. We show how the firm uses its pricing and production decisions to partition the uncertainty interval it faces and thereby influence the value of the information which it receives.
Keywords: 330; Mikroökonomik; Preistheorie